Friendship with a robot: Children's perception of similarity between a robot's physical and virtual embodiment that supports diabetes self-management. Issue 7 (July 2018) - Sinoo, Claudia; van der Pal, Sylvia; Blanson Henkemans, Olivier A.; Keizer, Anouk; Bierman, Bert P.B.; Looije, Rosemarijn; Neerincx, Mark A.
Highlights: Children feel stronger friendship for a physical robot compared to an avatar. When robot and avatar are perceived as similar, friendship with avatar is stronger. The stronger child's friendship with the avatar, the more user-friendly the app. The stronger child's friendship with the avatar, the more motivation to use the app. Combining physical and virtual embodiments could enhance motivation for health-apps. Abstract: Objective: The PAL project develops a conversational agent with a physical (robot) and virtual (avatar) embodiment to support diabetes self-management of children ubiquitously. This paper assesses 1) the effect of perceived similarity between robot and avatar on children's' friendship towards the avatar, and 2) the effect of this friendship on usability of a self-management application containing the avatar (a) and children's motivation to play with it (b). Methods: During a four-day diabetes camp in the Netherlands, 21 children participated in interactions with both agent embodiments. Questionnaires measured perceived similarity, friendship, motivation to play with the app and its usability. Results: Children felt stronger friendship towards the physical robot than towards the avatar. The more children perceived the robot and its avatar as the same agency, the stronger their friendship with the avatar was. The stronger their friendship with the avatar, the more they were motivated to play with the app and the higher the app scored on usability. Conclusion: The combination of physical and virtual embodiments seems to provide a unique opportunity for building ubiquitous long-term child-agent friendships. Practice implications: an avatar complementing a physical robot in health care could increase children's motivation and adherence to use self-management support systems.